2016
DOI: 10.1186/s13008-016-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

New insights into posttranslational modifications of Hippo pathway in carcinogenesis and therapeutics

Abstract: PTMs (posttranslational modifications) such as ubiquitylation, sumoylation, acetylation and protein methylation are pivotal modifiers that determine the activation, deactivation or subcellular localization of signaling proteins, facilitating the initiation, amplification and transduction of signaling. Accumulating evidence suggest that several key signaling molecules in Hippo signaling pathway are tightly regulated by various types of PTMs. Malfunction of these critical signaling modules such as YAP/TAZ, MAT1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 53 publications
0
54
0
4
Order By: Relevance
“…Accumulating evidence suggests that the Hippo-YAP pathway is tightly regulated by various types of posttranslational modifications, including phosphorylation, ubiquitination, sumoylation, acetylation, etc. (66). Our study reveals a mechanistic link between neddylation and Hippo signaling.…”
Section: Discussionmentioning
confidence: 70%
“…Accumulating evidence suggests that the Hippo-YAP pathway is tightly regulated by various types of posttranslational modifications, including phosphorylation, ubiquitination, sumoylation, acetylation, etc. (66). Our study reveals a mechanistic link between neddylation and Hippo signaling.…”
Section: Discussionmentioning
confidence: 70%
“…LATS1 mRNA levels were not affected by MG in the three breast cancer cell lines (Figure 6—figure supplement 1A). A previous study has shown that LATS1 kinase degradation occurs through polyubiquitination and the proteasome pathway in breast cancer cells (He et al, 2016). In good accordance, the treatment of breast cancer cells with MG132 proteasome inhibitor induced LATS1 increase (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased YAP phosphorylation can favor YAP retention in the nucleus. Phosphorylation of YAP at Ser-397 promotes its proteolytic degradation (18). The ratio of Ser-397 phosphorylated YAP to total YAP also decreased 7 days after TAC ( Fig.…”
Section: Yap Is Activated In Response To Pomentioning
confidence: 82%